Relative Importance of Quality Factors and Determinants in the Selection of Foreign Language Courses in Social Networks - Danielle Miranda de Oliveira Arruda Gomes; Cláudio André Gondim Nogueira; Gilmara Elke Dutra Dias (Universidad Nacional, Costa Rica, 2015)
This paper is based on a research of the relative importance of quality factors and determinants for the selection of language courses in a virtual environment, according to Lee e Kozar (2006). The method used was the Analytic Hierarchy Process. A survey was carried out with 200 individuals who had experiences with any type of educational service in the virtual environment. The more significant factor was the system's quality, followed by the quality of service, the quality of the information, and the quality of a specific vendor. The main sub-factors were responsiveness, response time, navigability, and security. The study concludes that better-structured social networks facilitate purchases and can induce consumers to change their behavior, moving from conventional to virtual environments. The discovery of the quality factor hierarchy for selecting the social network to study languages suggests that the developers should design websites that present more aesthetic, comfortable, and effective educational services provision, in accordance with the consumers' expectations.